Hello neighbor : a novel - Aril Daine (Quezon City : Creative Programs, 2019)
"College. A Clean slate. Wala na 'yung drama nung high school, " di na ako makukumpara sa best friend kong perfect, at wala na ang heartbreaker na si Derek. Only me, my short hair, and my bright beautiful future. But then, Engineer Gabriel Vaughn Rodriguez walks, barges into my life--literally! This annoying, noisy, super kulit, sometimes funny, and okay fine quite handsome young man moves in next door. And gusto niyang mag-dinner kami gabi-gabi. And he holds my hand. And tells me I'm beautiful. Nakakabaliw!"--Cover.
Keywords: Filipino fiction